(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2020)
This research aims to discuss an important issue because of its role in increasing the efficiency of financial markets and boost investor confidence by a insider trading, which arises as a result of leaking secret information to some investors and reliable in the process of trading shares in the Iraq Stock Exchange And thus obtain abnormal profits at the expense of other investors. Research was based on the assumption that " Where shortcomings in local regulations relating to disclosure and insider trading in accounting information leads to the activate the phenomenon of insider trading in accounting information in the Iraq Stock Exchange and including a negative impact on investors’ decisions ". and Because of the difficulty the discovery of insider trading activities has been used to measure the change in the volume of trading shares of certain companies before and after the announcement of the meeting and find out the direction of change (increase or decrease). This was done on the three companies. Among the most important findings of this research, is the lack of local laws and regulations from the processors to the phenomenon of insider trading which led to the activate this phenomenon in the Iraq Stock Exchange. The conclusions of the research need to benefit from the experiences of other countries in the formulation of laws on insider trading in accounting information has been